Hetman Żółkiewski i rok 1610 w tradycji romantycznej - Fiećko, Jerzy (Slavia Occidentalis, 2015)
The author looks into the reasons behind the infrequent mention of Hetman Żółkiewski and the Polish victory over Russia in 1610. To this end he analyses Russian (e.g. by Pushkin) and Polish texts (e.g. by Niemcewicz, Lelewel, Krasiński, Mickiewicz) which contain references to the so-called period of Great Sorrow. It is interesting to note that, compared to the strong presence of the Polish-Russian War of 1605–1612 in the Russian culture, Polish Romantics made scant references to these events. The explanation for this state of affairs seems to be the historiosophical strategy adopted by the Polish Romantics which required that one’s own country’s military achievements be ignored or made less relevant. The author also reconstructs the evolution of attitudes toward Hetman Żółkiewski in the Polish historical and literary tradition from the 17th to the 20th century.